Comparison of Incision and Drainage with Needle Aspiration in the Treatment of Breast Abscess - Areej Mubashir; Ayesha Tahir; Sadeeq Ahmad; Shahzad Ahmed (Pakistan Journal of Health Sciences, 2026)
Breast abscess is a common complication of mastitis in low- and middle-income countries and may impair cosmetic appearance and breastfeeding. Conventional incision and drainage (I/D) are effective but associated with scarring and delayed recovery. Ultrasound-guided needle aspiration is a minimally invasive alternative. Objective: To compare the efficacy of ultrasound-guided needle aspiration and I/D in the management of breast abscesses. Methods: This retrospective comparative study was conducted in the Department of Surgery, Hayatabad Medical Complex, Peshawar, from August to October 2025. A total of 110 female patients (18–60 years) with breast abscesses of ≥3 days duration was included using record-based sampling. Patients with BMI >29.9 kg/m², chronic diabetes, or recent breast intervention were excluded. Group A (n=55) underwent I/D, while Group B (n=55) received ultrasound-guided needle aspiration. All patients received antibiotics. The primary outcome was treatment success (complete resolution without recurrence). Data were analyzed using SPSS version 23.0, and a chi-square test was applied. A p-value